ASSISTANCE FROM INTERNATIONAL FORENSIC EXPERTS IN THE INVESTIGATION OF CRIMES OF POL POT'S REGIME IN CAMBODIA - Sh. Khaziev (Теория и практика судебной экспертизы, 2016)
In 2007 almost all of the leaders of the Cambodian «Khmer Rouge» that were still at large were arrested and brought to trial. Some of the more notorious figures involved in mass executions and torture were also arrested. Forensic experts from Cambodia and other countries conducted extensive work in collecting evidence of genocide and other serious crimes committed on the territory of the country, which provides valuable insights for specialists in the fields of international law, the criminal procedure, criminalistics and forensic science.